STUDI KASUS PEMILIHAN HINDU SEBAGAI AGAMA MASYARAKAT TENGGER - Zakia Sukha Jamilah; Faza Dhora Nailufar (Universitas Darul Ulum, 2021)
This paper intends to find out the reasons and backgrounds why the Tengger people chose their religion to Hinduism amid the invasion of major religions such as Islam and Christianity. In 1965, precisely after the emergence of Law No.1 / PNPS / 1965 concerning the prevention of misuse and or blasphemy of religions which were recognized by the state, people with traditional beliefs were required to choose religion they would write down on their ID card column. Most of the Tengger people choose to write